Economic assistance and security : rethinking US policy - Hough, Richard Lee, 1925- (Fort Lesley J. McNair, Washington, D.C. : National Defense University Press : For sale by the Supt. of Docs., U.S. G.P.O., 1982)
Contents: The Changing National Security Environment; The Program Framework of US Economic Assistance; The Policy Framework of US Economic Assistance; Program Issues; Program Perspectives; and Proposals for Change.
The Changing National Security Environment; The Program Framework of US Economic Assistance; The Policy Framework of US Economic Assistance; Program Issues; Program Perspectives; and Proposals for Change.
Item 378-H-1.
008-020-00895-8.
Includes bibliographical references.
Keywords: Economic assistance, American -- Developing countries; National security -- United States; Foreign aid; Natural resources; Food; Production; Population; Foreign policy; Economic assistance, American; Military policy; Developing countries